Opini Masyarakat Tentang Program Corporate Social Responsibility PT. Ukindo Blankahan Terhadap Masyarakat Sekitar - Br. Ginting, Adelia Indrayani (Universitas Muhammadiyah Sumatera Utara, 2023)
The purpose of this research is to find out the community's opinion about PT. Ukindo Blankahan's CSR program for the surrounding community. Blankahan's CSR program for the surrounding community that has been going on so far. Type of type of research used in this research is qualitative, because the authors trying to describe the results of interviews and reviewing directly to the research location. the research location. The analysis of data is done by using qualitative descriptive analysis method, i.e.describing the data obtained through the research instruments. qualitative analysis method, namely describing the data obtained through research instruments with 10 people. research instruments with 10 sources. The results of this study indicate that public knowledge about the Corporate Social responsibility program of PT. Ukindo Blankahan's Corporate Social responsibility program to the surrounding community is quite good. They know the overall CSR programs of PT Ukindo Blankahan.they also assess the Corporate Social responsibility program provided by PT. Ukindo Blankahan is good enough and is needed by the community. Bangun Rakyat Village and Laubuntu Village, the community gives a very positive value to the CSR programs of PT. almost all communities said they agreed with PT. Ukindo Blankahan's CSR programs.